Cyclooxygenase-2 expression in cervical squamous cell carcinoma: The significance of expression in neoplastic cells within the lymphovascular space - Jongkolnee Settakorn (2018)
Background: Cyclooxygenase-2 (COX-2) activity is related to the development and progression of cervical cancer. Previous studies have shown that COX-2 expression in early stage (stage IB-IIA) cervical squamous cell carcinoma is associated with lymph node metastasis in tumors with lymphovascular space invasion (LVSI), and that COX-2 expression may facilitate lymph node metastasis after LVSI occurs. In this study, we evaluated whether COX-2 expression of neoplastic cells within lymphovascular spaces (tumor emboli) would provide additional prognostic information. Methods: Immunohistochemical stained slides for COX-2 on 150 cases of stage IB-IIA cervical squamous cell carcinoma with LVSI were evaluated for expression of COX-2 in tumor emboli. Results were correlated with overall COX-2 expression of tumor and clinicopathologic features using statistical analysis. Results: Expression of COX-2 was detected in 49.3% of cases. Expression of COX-2 in tumor emboli (LV-COX-2 expression) was identified in 61 cases (40.7%). LV-COX-2 expression was associated with high LVSI count (p<0.001) and had a marginal association with tumor COX-2 expression (p=0.050) and lymph node metastasis (p=0.063). In tumors showing high LVSI count, LV-COX-2 expression was an independent predictor for lymph node metastasis (p=0.038, 95% CI=1.030-2.725) whereas tumor COX-2 expression (p=0.550) was not. Conclusion: Evaluation of COX-2 expression in tumor emboli may provide additional prognostic value for lymph node metastasis in cervical squamous cell carcinomas with a high LVSI count.